Bacterial Microbiota in Unfed Ticks (Dermacentor nuttalli) From Xinjiang Detected Through 16S rDNA Amplicon Sequencing and Culturomics - Song, Kai; Ji, Yuxin; Sun, Surong; Yue, Xihong; Wang, Cheng; Luo, Tao; Moming, Abulimiti; Song, Yajun; Zhang, Yujiang; Yang, Ruifu (Zoonoses (Burlington, Mass.), 2021)
Ticks are a major arthropod vector of zoonotic diseases affecting both humans and domestic animals worldwide. Thus, studying tick microbiota would aid in understanding of the potential threats posed by ticks. Approximately 8,000 unfed ticks, identified as Dermacentor nuttalli , were collected from the sylvosteppe in the western Tianshan mountains. To investigate their potential pathogens, we divided the ticks into 36 groups of 200–300 individuals each for examination with culturomics and 16S rDNA amplicon sequencing. A total of 237 bacterial genera were identified with the two methods. Culturomics identified 46 bacterial species from 23 genera, predominantly Pseudomonas , Pantoea , and Bacillus , whereas 16S rDNA sequencing identified 461 OTUs from 233 genera, predominantly Pseudomonas (53.8%), Coxiella (17.2%), and Pantoea (6.4%). Coxiella , Rickettsia , and ten other genera were discovered only by sequencing, because optimal cultivating conditions were not used for their isolation, whereas Arthrobacter and three other genera were discovered only through culturomics. Several of the identified bacteria, such as line-related sepsis-causing Delftia acidovorans and the pneumonia agent Acinetobacter pittii , can cause human diseases. Thus, both sequencing and culturomics methods are crucial for comprehensive understanding of the microbiota of D. nuttalli .